18.2k views
4 votes
Px + qx = r
solve for q

2 Answers

3 votes

Simplify both sides of equation and then isolate the variable your answer should be

q =
(r)/(2x)

Hopefully this helps ^0^ Mark Brain

User Czlowiekwidmo
by
5.5k points
2 votes

Answer:

q = (r - px) / x

or you could write it as q = (r/x) - p

Explanation:

px + qx = r

qx = r - px

q = (r - px) / x

User Wmakley
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.